2017
DOI: 10.1080/15287394.2016.1260508
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate in drinking water and risk of colorectal cancer in Yogyakarta, Indonesia

Abstract: Nitrate concentration in well water in Yogyakarta, Indonesia, and its surroundings tended to increase rapidly from time to time, and it may be associated with an elevated risk for several types of cancer. The purpose of this study was to examine the association between nitrate in drinking water and colorectal cancer (CRC) risk occurrence. A case-control study was conducted in Yogyakarta Special Province. Pathologically confirmed 75 CRC patients and 75 controls were consulted and their individual well water was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 25 publications
1
15
0
2
Order By: Relevance
“…There were no interactions with red meat, vitamins C and E, and fiber except for a borderline interaction ( p -interaction = 0.07) for rectum cancer with fiber intake. A small hospital-based case-control study in Indonesia found that drinking water nitrate levels above the WHO standard (>11.3 mg/L as NO 3 -N) was associated with colorectal cancer [ 136 ]. A national registry-based cohort study in Denmark [ 32 ] evaluated average nitrate concentrations in PWS and private wells in relation to colorectal cancer incidence among those whose 35th birthday occurred during 1978–2011.…”
Section: Cancermentioning
confidence: 99%
“…There were no interactions with red meat, vitamins C and E, and fiber except for a borderline interaction ( p -interaction = 0.07) for rectum cancer with fiber intake. A small hospital-based case-control study in Indonesia found that drinking water nitrate levels above the WHO standard (>11.3 mg/L as NO 3 -N) was associated with colorectal cancer [ 136 ]. A national registry-based cohort study in Denmark [ 32 ] evaluated average nitrate concentrations in PWS and private wells in relation to colorectal cancer incidence among those whose 35th birthday occurred during 1978–2011.…”
Section: Cancermentioning
confidence: 99%
“…Indeed, a significant number of studies have found an association between exposure to a relatively high nitrate concentration and the risk of developing cancer. Examples of such studies include case-con- research conducted by Fathmawati et al (2017) in Indonesia. The findings demonstrated (after adjusting for smoking history, age, and family history of cancer) an association between prolonged exposure (more than 10 years) to nitrate concentration in drinking water above 11.29 mg/L of nitrate as N, with an increased risk of colorectal cancer occurrence (OR = 4.31; 95% CI: 1.32-14.09).…”
Section: Discussionmentioning
confidence: 99%
“…De acuerdo con el valor del IRCApp promedio anual, los 29 acueductos restantes se distribuyeron, según nivel de riesgo, de la siguiente manera: seis [6] en nivel de riesgo bajo, doce [12] en nivel de riesgo Medio y once [11] en nivel de riesgo Alto, lo que, según la norma Colombiana, significa que suministraron agua no apta para consumo humano.…”
Section: Discussionunclassified